THE IMPACT OF ENERGY CONSUMPTION ON ECONOMIC GROWTH IN SOUTH ASIAN COUNTRIES - Ruhul , S; Rafiq, S; Hassan , A. K. (Economics and Statistics Research Journal (ESRJ), 2022)
This study examines the relationship between energy consumption and economic growth in South Asian countries using macroeconomic determinants such as foreign direct investment (FDI) growth, the consumer price index (CPI) rate, and population growth from 1980 to 2019. The study uses panel data models such as pooled regression, fixed effects, bidirectional fixed effects, random effects, and GLS estimation regression models to analyze the significant relation of these determinants and the impact of energy consumption on economic growth. The results show a positive correlation between energy consumption and all other economic determinants of economic growth, except for CPI, where a negative correlation was found. This study aims to enrich the existing literature on this subject matter, as the causality between energy consumption, FDI, CPI, population growth, and economic growth in South Asia has not been previously examined.